PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D. E. Medio; NICOLÁS PERAGÓN, J. L.; DOMINGUEZ LERENA, S.; HERRERO SIERRA, N.; VILLAR- SALVADOR, P. (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage